Somatization as a Predictor of Outcomes Following Functional Restoration of Chronic Disabling Occupational Musculoskeletal Pain Disorder Patients. Issue 2 (25th June 2013) - Hartzell, Meredith M.; Choi, Yunhee; Neblett, Randy; Williams, Mark; Mayer, Tom G.; Gatchel, Robert J.
<x xml:space="preserve">Abstract</x> Chronic disabling occupational musculoskeletal pain disorder (CDOMPD) patients often have high levels of somatization, a phenomenon in which somatic symptoms are medically unexplainable. Examination of 1, 458 CDOMPD patients, who completed the patient health questionnaire (PHQ) somatization module from 2003 to 2010 and underwent functional restoration treatment, were divided into low, moderate, and high somatization at pretreatment. Somatization was highly responsive to treatment, and those with high somatization reported the highest depressive symptoms, disability, and pain intensity, and the lowest health‐related quality of life at pre‐ and post‐treatment. Somatization levels significantly predicted 1‐year socioeconomic outcomes of work return, work retention, and healthcare utilization. High somatization may act as a "red flag" for clinicians, indicating patients may be at risk for poor treatment outcomes.